Grounded Theory-Based User Needs Mining and Its Impact on APP Downloads: Exampled With WeChat APP - Chen, Tinggui; Zhang, Chu; Yang, Jianjun; Cong, Guodong (Frontiers in Psychology, 2022)
Software development is an iterative process from designing to implementation, and to testing, in which product development staff should be closely integrated with users. How to closely combine with users’ needs is often the pain point of developers. In order to alleviate this pain point, this paper tries to use mathematical calculation to establish the connection between users and products, to provide reference for software development how to establish the connection with users and app (Application Program) development companies and users have interacted closer and closer under web 2.0. Generally, for companies, the analysis of user online comments can dig out user demands and preferences, pinpoint the market position of app products, and iteratively innovate products based on the demand information of app users, thereby increasing the volume of app downloads. This paper takes WeChat app as the research object. Firstly, we capture user online comment data during 47 update periods. Then based on Grounded Theory, we mine the users’ needs from online comments after cleaning. Next word frequency analysis, sentiment analysis and semantic analysis are used to quantify user needs. Finally, we construct a quantile regression model to study the impact of user demand on downloads so as to provide a decision basis for enterprises to iteratively update their products. The results demonstrate that: (1) The main demands of WeChat users include performance, reliability, usability, functionalities to be added, functionalities to be improved, and differentiated requirements of different operating systems; (2) When the volume of app downloads is low, users’ demands are the functionalities to be added, functionalities to be improved, performance, availability, and the differentiated requirements of different operating systems. When the volume of app downloads is moderate, the user’s demands are functionalities to be added, the functionalities to be improved, and the differentiated requirements for different operating systems. In addition, when the volume of app downloads is high, users’ demands are performance, usability, and differentiated requirements for different operating systems.